LIFE SHIFTING PHENOMENA OF SAKAI WOMEN IN RIAU - Sukma Erni; Cut Raudhatul Miski (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This research aims to explore the life shifting phenomena of Sakai women in the modernity era. The research based on the phenomenon of Sakai women living in off the beaten track of rural areas in which communication with outsider is extremely limited. Living with traditional patterns that handed down from generation to generation, their social shift occurs very slowly. Up to this moment, they are still at a marginal level; where the level of education, public social participation, and economic level is considered low still.. This study was carried out using phenomenological qualitative methods by looking at and exploring phenomena into structured concepts so that they were easy to understand. The study involved 10 key informants, six women including the village head and four men. The research findings explain that the cultural shift towards change in the Sakai women more created through the assimilation between ethnic groups. It leads to cultural interaction which is built positively, the coercion of situations that force to stay settled, living side by side with the outside of Sakai community, exposure to the social environment and TV media have change their life style.